Gemella endocarditis. (2022) - Rabah, Hussein; El Gharib, Khalil; Assaad, Marc; Kassem, Ali; Mobarakai, Neville
Abstract: We herein present the case presenting to our facility complaining of a fever of two months duration, who underwent dental procedure. Patient was diagnosed with infective endocarditis secondary to an uncommon bacteria: Gemella haemolysans . Patient was found to have concomitant severe mitral valve regurgitation. Our patient did not have any comorbidity or risk factor beside his dental procedure. Our patient received intravenous antibiotic therapy for six weeks and was scheduled for mitral valve replacement.